CONTENT VALIDITY OF PBL TUTORIAL INSTRUMENT FOR PROBLEM-BASED LEARNING - Nindya Aryanty; Siti Raudhoh; Rita Halim (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: Problem-based Learning (PBL) is characterized by tutorial learning method where learning triggered using structured scenarios to initiate and stimulate student discussion in a small group, with facilitation by a tutor. Student performance during tutorial should be assessed by the tutor. Sim et al. from the University of Malaya developed PBL Tutorial Instrument measuring participation and communication ability, cooperation/team building skills, understanding/ reasoning skills, knowledge/skills gathering information. PBL Instrument Objective: This study aims to construct a new valid tutorial assessment instrument through adaptation and modification of the previous instrument developed by Sim et al. Method: This study consisted of 3 stages: forward translation, backward translation, and expert review. Forward translation is the process of translating instruments from English to Indonesian language. The results of the forward translation are given to different translators for a backward translation process. Instrument then submitted to seven experts to be validated and provide suggestions regarding the content and sentences used in the instrument items. The content validation process is carried out using the CVI and S-CVI score. Results: Forward and backward translation results shows that 20 items in the instrument were confirmed to be consistent with the original instrument. However, the first round of content validity process resulted I-CVI score for every item is â‰¥ 0.86 and the S-CVI score 0.99. Several experts suggested revision for item sentences corresponding with actual PBL implementation in the institution. Items were revised then the same experts then re-validated the revised instrument. Result showed the I-CVI and S-CVI score are 1.00. Conclusion: This research produced a valid Indonesian language version of the PBL assessment instrument, so that it can be used as an instrument to evaluate student performance in tutorial. Pilot studies need to be carried out further to obtain an analysis of the validity and reliability of the instrument. Keyword: instrument, PBL Tutorial, assessment